The Estimation Uncertainty Measurement for Personal Dosimetry Use for Dose Audit by Analytical Method and Monte Carlo Simulation Method - Pungkun, Vithit; Rindhatayathon, Pongphanot; Phapakhee, Theraporn (Burapha Science Journal, 2026)
The personal dosimetry measurement is important for monitoring radiation workers or quality control. Present, Optically Simulated Luminescence (OSL), nanoDot dosimeter uses for medical dosimeter, was selected to evaluate the uncertainty for the personal dose system for quality control of Office of Atoms for Peace. The dosimeter wes irradiated at 4.35 mSv of Cs-137 and evaluated their uncertainty. The uncertainty was combined from Inhomogeneity of detector sensitivity, Variability of detector reading due to limited sensitivity and background, Variability of detector reading at zero dose, Energy and direction dependence, Non-linearity of response, Fading, dependence ambient temperature and humidity and variation in local natural background, Effects of light, Calibration error, Correction error for reading algorithm. The combination uncertainty result, the reading dose is 4.60 ± 1.42 mGy at a 95% confidence with the analysis method. This is similar to the calculation using the Monte Carlo modeling method that shows the dose is 4.44 ± 1.32 mGy at a 95% confidence level.